AI in qualitative research: Using large language models to code survey responses in native languages - Singh, Tushar; Kumar, Himangshu (International Food Policy Research Institute, 2025)
Food systems research - and more generally, policy and development research -often relies on structured surveys, administrative data, or experiments. While these approaches yield valuable quantitative insights, they tend to miss critical qualitative dimensions. One useful qualitative approach is open-ended interview questions. When such responses are collected in participants' native languages, they can provide rich and nuanced information-for example, on the complex local challenges smallholder farmers face.